The silence between us - Gervais, Alison (Grand Rapids, Michigan : Blink, 2019)
After moving to Colorado, deaf seventeen-year-old Maya is forced to attend a hearing school, where she must navigate a new life and prove that her lack of hearing will not stop her from pursuing her dreams. Includes an interview with the author.
Ages 13+.
Keywords: Deaf -- Fiction; Dating (Social customs) -- Fiction; Cystic fibrosis -- Fiction; Family life -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction